Melatonin Improved the Survival of Multi-Territory Perforator Flaps by Promoting Angiogenesis and Inhibiting Apoptosis via the NRF2/FUNDC1 Axis - Huang, Chengxiong; Qing, Liming; Pang, Xiaoyang; Fu, Jinfei; Xiao, Yu; Tang, Juyu; Wu, Panfeng (Frontiers in Pharmacology, 2022)
Background: Multi-territory perforator flaps are a reconstructive measure for repairing large soft tissue defects caused by tumors or trauma. However, the use of these flaps in clinical practice has been restricted due to the uncertain blood supply. Therefore, promoting the survival of the multi-territory perforator flap is critical for clinical repair and reconstruction. In our study, we explored the effects of melatonin (MLT) on multi-territory perforator flaps and the possible molecular mechanisms. Materials and methods: Seventy-two Sprague–Dawley rats (250-300 g) were randomly divided into 3 groups (n=24): Control, MLT and MLT+ML385 groups. First, we assessed the survival area of the flap, followed by the micro-vessel density and CD31-positive vessel expression. Apoptosis of the skin flap under immunofluorescence and expression of the apoptosis-related proteins Bcl-2, Bax and Caspase3 were measured. Additionally, angiogenesis of the skin flaps was shown by angiography, and NRF2 and FUNDC1 mRNA and protein expression was detected by real-time PCR and western blotting. Results: The results showed that MLT increased the survival area of the multi-territory perforator flap, which was related to increased angiogenesis and decreased apoptosis. We also found that mRNA and protein of NRF2 and FUNDC1 levels were significantly increased after MLT treatment, and an NRF2 inhibitor reversed the ability of MLT to enhance multi-territory perforator flap survival, promote angiogenesis and inhibit apoptosis and reduced FUNDC1 protein expression. Conclusion: MLT promoted angiogenesis and inhibited apoptosis to promote the survival of multi-territory perforator flaps, which may be regulated via the NRF2/FUNDC1 axis.